Properties of the hypergeometric function type I distribution (2005)
ABSTRACT: The hypergeometric function type I distribution with the pdf proportional to x () ( ) − x F α β γ − x ν− γ− 1 2 1 , ; ; 1 1 1 occurs as the distribution of the product of two independent beta variables. In this article, we study several properties and stochastic representations of this distribution.